IMPLEMENTASI LITERASI DIGITAL UNTUK MENINGKATKAN KEMAMPUAN SISWA SEKOLAH MENENGAH PERTAMA (SMP) (Studi Kasus di SMPN 1 Campaka Kabupaten Purwakarta) - Iva Khairun Nissa; Suci Indriany; N. Mumun Mulyawati; Uman Gunawan; Dinny Mardiana (STKIP Subang, 2026)
The development of digital technology has brought significant changes to the field of education, particularly in the learning process at schools. Digital literacy has become an essential competency that students need to master in order to meet the challenges of 21st-century education. This study aims to describe the implementation of digital literacy in improving the abilities of junior high school students. The study employed a qualitative approach using a case study method conducted at SMPN 1 Campaka, Purwakarta Regency. The research participants consisted of the principal, teachers, and students. Data were collected through observation, interviews, and documentation. Data analysis was carried out using the Miles, Huberman, and Saldaña model, which includes data reduction, data display, and conclusion drawing. The findings revealed that digital literacy was implemented through the utilization of various digital media and platforms, such as Google Classroom, Canva, Educational YouTube, Interactive PowerPoint, and the internet as learning resources. The implementation of digital literacy had a positive impact on students’ abilities, as reflected in the improvement of digital information comprehension, learning motivation, classroom participation, technology utilization skills, and critical thinking skills. However, several challenges were identified, including limited digital facilities, unstable internet connectivity, and unequal technological competencies among teachers and students. Therefore, continuous efforts are required to improve digital infrastructure and competencies in order to optimize the implementation of digital literacy in schools